Jun ware glazes: Chemistry, nanostructure and optical properties. Issue 12 (September 2018) - Hou, Jiayu; Pradell, Trinitat; Li, Yuan; Miao, Jianmin
Abstract: A set of the Classic and official Jun ware shards found at various kilns at Yuzhou (Henan) are analyzed. The blue color and milky appearance of the glazes subject of intense debate as being due to either the glaze nanostructure or chemistry. The presence of submillimetre areas showing different color and opacity gives to the glazes a three dimensional cloudy sky appearance. Nanostructure and chemistry of the glazes, oxidation state of iron and nature of the copper nanoprecipitates are studied at a submillimetre level. Images of the glaze nanostructures are obtained using a Focus Ion Beam and Scanning Electron Microscope with nanometric resolution. The size and volume fraction of the nanostructures determined by image treatment are related to the chemical composition of the glazes. Differences between kiln productions are found and the origin of the color and opacity of the glazes discussed in terms of the chemistry and nanostructure.